أهمية الليدوكائين الوريدي في تسكين الألم عند مرضى الجراحات البطنية الكبرى - سلامه, عبد الهادي; إبراهيم, رزق الله; داؤد, ديما (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي باللاذقية في قسم التخدير والإنعاش خلال عام 2008- 2009 وتضمنت 100 مريض خضع كل منهم لعمليه جراحية كبرى إذ تم استخدام الليدوكائين الوريدي // دفش ثم تسريب // خلال العمل الجراحي. تم تقسيم المرضى إلى مجموعتين: المجموعة الأولى (A): 50 مريض تم استخدام الليدوكائين الوريدي دفش بجرعة 1.5 ملغ/ كغ ثم تسريب بجرعة 2 ملغ/ كغ/ سا المجموعة الثانية (B): 50 مريض تم تسريب حجم معادل من محلول سالين . كان هدف هذه الدراسة معرفة تأثير الليدوكائين من جهة تخفيف جرعة المورفينات المستخدمة للتسكين في أثناء وبعد العمل الجراحي والتقليل من نسبة حدوث العلوص الشللي بعد العمل الجراحي والتقليل من مدة استشفاء المريض. وكانت نتيجة البحث: انخفاض جرعة المورفينات المستخدمة أثناء وبعد العمل الجراحي لدى المجموعة A. This study was carried out in the department of Anaesthesia and Resuscitation at AL-ASSAD University Hospital in Lattakia during 2008-2009 and included 100 patients who had undergone a major abdominal surgery. Intravenous Lidocaine was used <buls and infusion > during the operation. Patients chosen were divided into two groups. After administering a bolus injection of Ledocaine 1.5 mg\kg and infusion (2mg \kg\h.Iv), the first group (50 patients) used intravenous lidocaine during the operation.. The second group (50 patients) used an infusion of an equal volume of saline. The objective of this study was to detect effect of lidocaine that lessened morphine consumption during and after operation and reduced postoperative paralytic ileus, making patient hospitalization shorter. This research resulted in reducing the morphine dose in the first group during and after operation.